Anatomy of forest-related corruption in Tanzania: theoretical perspectives, empirical explanations, and policy implications. Issue 2 (4th May 2017) - Perfect-Mrema, Joseph
ABSTRACT: The majority of studies on natural resources management in both developed and developing countries are silent on the issue of analysis of corruption – or they treat it tangentially, as an annoying anomaly, or simply deviance from the rules. As a result, the issue has hardly been subjected to in-depth characterisation or reforms. This study employed and integrated mainstream principal-agent theory and more recently developed collective action theory to enhance our understanding – in different but complementary ways − of the socio-political underpinnings of corruption. A supposed 'best case' participatory forest management scheme in Tanzania reveals significant forest-related corrupt undertakings, which led to forest encroachment in the form of charcoal and timber exploitation. The findings point to contextual grounds for corruption, namely: undermined assumptions of the mainstream principal-agent institutions; the presence of alternative informal principal-agent institutions; the presence of immediate and substantial benefits that flow to such alternative institutions; and the huge market demands for their forest products and services. Through such a nuanced approach that blends the two above-mentioned theories in meaningful ways, more appropriate options for policy formulation and implementation are proposed.